Potency of Garlic (Allium sativum) Extract Against Motile Aeromonad Septicaemia Disease Caused by Aeromonas hydrophila in Pangasionodon hypophthalmus - Yuhana, M.; Normalina, I.; Sukenda, . (Jurnal Akuakultur Indonesia, 2008)
An infectious disease caused by motile members of the genus Aeromonas, is among the most common diseases of fish cultured in freshwater, including the Thai catfish, Pangasionodon hypophthalmus. Motile aeromonad infections have been recognized for many years by various names, including motile aeromonad septicemia (MAS), motile aeromonad infection (MAI), hemorrhagic septicemia, red pest, and red sore. In our experiment, we study the potency of a phytopharmacia agent, garlic extract for prevention and curing off the experimental infections by Aeromonas hydrophila. In series of in vitro assays, the garlic extract showed inhibition capacity on the bacterial growth. The extract dosage of 25 mg/ml (2.5 g/l) was found to be the most effective among other dosages i.e 1, 2, 5, 10, 20, 50, respectively. Whereas in an in vivo assay using 25 mg/ml, it showed to be the most effective dosage for prevention against the intramuscularly experimental injection of A. hydrophila rather than as a curing agent. Keywords:  Pangasionodon hypophthalmus, Allium sativum, dan Aeromonas.   ABSTRAK Salah satu penyakit yang sering menyerang ikan patin (Pangasionodon hypophthalmus) dan ikan air tawar lainnya adalah penyakit MAS (Motile Aeromonad Septicemia). Penyakit ini juga dikenal sebagai penyakit bercak merah yang disebabkan oleh bakteri Aeromonas hydrophila dan mudah menular. Secara in vitro, ekstrak bawang putih (Allium sativum) berpotensi sebagai antibakteri yang dapat menghambat pertumbuhan bakteri A. hydrophila. Dosis ekstrak bawang putih sebesar 25 mg/ml (2,5 g/l) merupakan dosis  yang efektif untuk menghambat pertumbuhan A. hydrophila pada uji in vitro. Pada uji in vivo ekstrak bawang putih yang disuntikkan terhadap ikan patin, dengan dosis ekstrak sebesar 25 mg/ml (2,5 g/l) menunjukkan hasil yang lebih efektif dalam mencegah infeksi A. hydrophila dibandingkan pengobatan. Kata kunci: patin, Pangasionodon hypophthalmus, bawang putih, Allium sativum, MAS dan Aeromonas.